Inaccuracy of brachial blood pressure and its potential impact on treatment and aortic blood pressure estimation. Issue 12 (December 2021) - Kowalski, Cédric; Yang, Katie; Charron, Thierry; Doucet, Michel; Hatem, Raja; Kouz, Rémi; Palisaitis, Donald; Schampaert, Erick; Terriault, Paul; Tessier, Pierre; Agharazii, Mohsen; Goupil, Rémi
Abstract : Objective: Although brachial cuff SBP is universally used to guide hypertension management, it can differ significantly from intraarterial SBP. We examine the potential impacts of cuff-to-intraarterial brachial SBP (bSBP) mismatch on hypertension treatment and accuracy towards central SBP. Methods: In 303 individuals, cuff bSBP (CUFF- bSBP) and central SBP were measured using a Mobil-o-Graph simultaneously to intraarterial bSBP (IA- bSBP) and aortic SBP. According to the difference between CUFF- bSBP and IA- bSBP, we identified three phenotypes: Underestimation (CUFF- bSBP < IA- bSBP by >10 mmHg); No Mismatch (CUFF- bSBP within 10 mmHg of IA- bSBP); Overestimation (CUFF- bSBP > IA- bSBP by >10 mmHg) phenotypes. Risk of overtreatment and undertreatment, and accuracy (ARTERY society criteria: mean difference ⩽5 ± 8 mmHg) were determined. A multiple linear regression model was used to assess variables associated with the bSBP difference. Results: Underestimation ( n = 142), No Mismatch ( n = 136) and Overestimation ( n = 25) phenotypes had relatively similar characteristics and CUFF -bSBP (124 ± 17, 122 ± 14, 127 ± 19 mmHg, P = 0.19) but different aortic SBP (133 ± 21, 120 ± 16, 112 ± 18 mmHg, P < 0.001). In the underestimation phenotype, 59% were at risk of undertreatment (14% in No Mismatch), whereas 50% in the Overestimation phenotype were at risk of overtreatment (17% in No Mismatch). CUFF- bSBP accurately estimated aortic SBP only in the No Mismatch Group (mean difference 1.6 ± 8.2 mmHg) whereas central BP never met the accuracy criteria. Male sex, higher height and active smoking were associated with lesser underestimation of bSBP difference. Conclusion: The brachial cuff lacks accuracy towards intraarterial BP in a significant proportion of patients, potentially leading to increased risks of BP mismanagement and inaccurate determination of central BP. This illustrates the need to improve the accuracy of cuff-based BP monitors. Abstract : Supplemental Digital Content is available in the text